Hubungan Jumlah dan Jenis Leukosit dengan Kadar Creatine Kinase Myocardial Band (CK-MB) pada Penderita Sindrom Koroner Akut: Correlation Between Leukocyte Differential Count and Creatine Kinase Myocardial Band (CK-MB) in Patient with Acute Coronary Syndrome - Andi Zsazsa Rafiatul Mukhlis; Bunga Anggreini Sari (LPPM STIKES Guna Bangsa Yogyakarta, 2026)
Background: Acute Coronary Syndrome (ACS) remains a major cause of morbidity and mortality worldwide. Inflammatory responses involving leukocytes play an important role in plaque instability and myocardial injury. Objectives: This study aimed to analyze the correlation between leukocyte differential count and creatine kinase myocardial band (CK-MB) levels in patients with ACS. Methods: This study used a retrospective cross-sectional design based on secondary data from the medical records of 126 ACS patients admitted to RSUD Ulin Banjarmasin in 2017. Total leukocyte count, neutrophil count, lymphocyte count, and CK-MB levels were collected and analyzed using linear regression analysis. Results: The analysis showed a significant positive correlation between total leukocyte count and CK-MB levels (p = 0.001), indicating that higher leukocyte counts were associated with greater myocardial injury. In contrast, lymphocyte count demonstrated a significant positive correlation with CK-MB levels (p = 0.003). However, neutrophil count showed no significant correlation with CK-MB levels. Conclusions: Leukocyte and lymphocyte counts were significantly associated with CK-MB levels in ACS patients, suggesting their potential role as simple inflammatory markers related to myocardial injury.